2019
DOI: 10.1002/bjs5.50143
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of an enhanced recovery after surgery programmeversusconventional care in laparoscopic Roux‐en‐Y gastric bypass surgery

Abstract: Background Enhanced recovery after surgery (ERAS) programmes have led to a decreased duration of hospital stay in several surgical fields, but have not been fully tested in patients undergoing laparoscopic Roux‐en‐ gastric bypass (LRYGB) for obesity. This study aimed to investigate an ERAS programme versus standard care in these patients. Methods Between January 2013 and July 2014, patients undergoing LRYGB were randomized to ERAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 29 publications
0
46
0
1
Order By: Relevance
“…Meta-analyses were conducted in R using random effects models with a maximum likelihood estimator. The median was used to estimate mean values for studies where length of stay was only reported as a median and range, and, as the sample size was greater than 70 for each of these studies, range/6 was used to estimate standard deviation [30,36,37]. Sensitivity analysis excluding these studies produced the same result as the primary analysis (S1 Fig) . A maximum likelihood estimator was chosen as simulation studies have demonstrated this to have suitable properties for estimating between-study variance [38,39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses were conducted in R using random effects models with a maximum likelihood estimator. The median was used to estimate mean values for studies where length of stay was only reported as a median and range, and, as the sample size was greater than 70 for each of these studies, range/6 was used to estimate standard deviation [30,36,37]. Sensitivity analysis excluding these studies produced the same result as the primary analysis (S1 Fig) . A maximum likelihood estimator was chosen as simulation studies have demonstrated this to have suitable properties for estimating between-study variance [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…While previous meta-analyses have compared outcomes between ERPs and conventional care in bariatric surgery, the authors of these analyses have noted the limited evidence base that informed them [28,29]. The literature searches to inform these analyses were conducted in 2016 and 2017, respectively, and with the recent publication of additional comparative studies this study sets out to evaluate what evidence gaps remain around the use of ERPs for LRYGB, LSG and OAGB [30][31][32]. A systematic literature review (SLR) was therefore carried out to identify recent clinical studies and clinical practice guidelines describing the use of any ERP in comparison with conventional care for patients undergoing these procedures across Europe, the Middle East and Africa (EMEA).…”
Section: Introductionmentioning
confidence: 99%
“…As adoption of ERPs may vary, with some elements implemented before others and differing rates of adoption across hospitals and countries, what constitutes 'conventional care' in one study may more closely resemble an 'ERP' in another. This may explain why in the study by Geubbels et al (2019) both treatment arms have a length of stay under 24 hours whereas all other studies report a length of stay of at least 1 day in either arm [30]. Geubbels et al (2019) reported no significant difference in median total length of stay between ERP (21.3 hours) and conventional care (21.2 hours) groups, however the primary outcome was median functional hospital stay (time from the end of surgery until all discharge criteria had been met) which was significantly shorter with the ERP (17.4 vs 20.5 hours, p<0.001), suggesting that patients in the ERP group could have been discharged even earlier [30].…”
Section: Plos Onementioning
confidence: 92%
“…This may explain why in the study by Geubbels et al (2019) both treatment arms have a length of stay under 24 hours whereas all other studies report a length of stay of at least 1 day in either arm [30]. Geubbels et al (2019) reported no significant difference in median total length of stay between ERP (21.3 hours) and conventional care (21.2 hours) groups, however the primary outcome was median functional hospital stay (time from the end of surgery until all discharge criteria had been met) which was significantly shorter with the ERP (17.4 vs 20.5 hours, p<0.001), suggesting that patients in the ERP group could have been discharged even earlier [30]. An additional factor could be variation in the discharge criteria used, although where reported these were broadly similar across the studies and therefore unlikely to be a major source of variation (S12 Table).…”
Section: Plos Onementioning
confidence: 92%
“…Meta-analyses were conducted in R using random effects models with a maximum likelihood estimator. The median was used to estimate mean values for studies where length of stay was only reported as a median and range, and, as the sample size was greater than 70 for each of these studies, range/6 was used to estimate standard deviation [30,36,37]. Sensitivity analysis excluding these studies produced the same result as the primary analysis (S1 Fig).…”
Section: Methodsmentioning
confidence: 99%